Analisis Curah Hujan terhadap Kesesuaian Jadwal Pemupukan NPK pada Budidaya Kelapa Sawit - Yuliyanto . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Rainfall is one of the factors of oil palm growth. Rainfall analysis needs to be done in the determination of NPK fertilization schedule. Large rainfall for application of fertilizer is 60 – 300 mm/month, while the optimal amount is 100 – 200 mm/month. This study aims to determine the most appropriate time for the application of NPK fertilizers and to know the effect of rainfall on the application of NPK fertilizer. This research was conducted in April 2017 at PT Cisadane Sawit Raya, Labuhan Batu Regency, North Sumatera Province. The method used in the implementation of this study is descriptive analysis method that is by analyzing the data available and processed so that obtained a clear picture of the facts and the relationship between the phenomena studied. The parameters observed are the amount of rainfall in the last 5 years in PT Cisadane Sawit Raya plantation. The results show that the optimal time for NPK fertilizer application is in June with 112.5 mm/month rainfall for the first rotation and in December with rainfall 201.8 mm/month for second rotation.